Analysis Bioeconomy Anchovies Rice (Stolephorus commersonii) in Labuhanbatu District Water of North Sumatera Province - Nasution, Yulinda Suaseh; Hendrik, Hendrik; Warningsih, Trisla (Jurnal Perikanan dan Kelautan, 2018)
Research on analysis resources bioeconomy anchovies rice has been implemented in August 2017 in waters Labuhanbatu North Sumatera. The purpose of this research to estimate Maximum Sustainable Yield (MSY) and Maximum Economic Yield (MEY), Effort Maximum Sustainable Yield (EMSY), effort Maximum Economic Yield (EMEY) and Effort Open Acces (EOA) resources anchovies rice in waters Labuhanbatu District. This research in a survey by analysis of data used the bioeconomy Gordon-Schaefer model. The result showed that the catch maximum sustainable (MSY) anchovies rice in waters Labuhanbatu District of 8,934.71 tons/years and Effort Maximum Sustainable Yield (EMSY) namely 47,379 trip/years, Maximum Economic Yield (MEY) anchovies rice namely 8,828.51 tons/years and Effort Maximum Economic Yield (EMEY) namely 42,213 trip/years and Effort Open Acces 84,427 trip/years. Profit level acquired while MSY Rp. 2,299,906.65 per years and MEY Rp. 2,334,868.58 per years. Based on analysis Gordon-Schaefer obtained model that production of actual anchovies rice in waters Labuhanbatu North Sumatera are still under the potential sustainable.